Access to and perceived unmet need for mental health services and support in a community sample of UK adolescents with and without experience of childhood adversity - Soneson, E; White, SR; Howarth, E; Ford, TJ; Fazel, M; Jones, PB (Cambridge University Press, 2024)
Aims. Children and adolescents with a history of adverse childhood experiences (ACEs) are more likely than their peers to develop mental health difficulties, but not enough is known about their help-seeking behaviours and preferences. We aimed to determine whether and how ACEs are associated with access to and perceived unmet need for mental health services and support amongst secondary school students.